8PComparison of standard uptake value of 18F-FDG-PET-CT with tumour-infiltrating lymphocytes in breast cancer ≥1cm. (24th November 2019) - Park, S; Min, E K; Bae, S J; Cha, C; Kim, D; Lee, J; Cha, Y J; Jeong, J; Ahn, S G
Abstract: Background: Tumor metabolism and tumor-specific immune responses are one of integral compartments consisting of tumor niche. Several lines of evidence showed that tumor cells and tumor-infiltrating lymphocytes (TILs) compete for glucose in tumor microenvironment and that tumor metabolic parameter correlates with localized immune markers in several solid tumors. With this background, we compared standardized uptake value (SUV) of 18F-fluorodeoxyglucose positron emission tomography-computed tomography (18F-FDG-PET-CT) and stromal TILs in breast cancer (1≥cm). Methods: Two hundred two patients were identified among those who underwent preoperative 18F-FDG-PET-CT and had tumor size equal to or larger than 1cm. Maximum SUV was obtained from 18F-FDG-PET-CT. Stromal TILs was evaluated according to standardized methodology proposed by the international TIL Working Group. We identified factors related with high TILs (≥40%) using multiple logistic-regression. All tumors were treatment-naïve. Results: There was a significant but weak correlation between continuous SUV and continuous TILs (p = 0.002, R = 0.215). Mean TILs was significantly high in Ki-67 labeling index ≥14%, nuclear/histologic grade 3, and HER2-positive or triple-negative breast cancer (TNBC). In multivariable analysis, aggressive subtypes as HER2-positive or TNBC and continuous SUV were significantly associated with high TILs ≥40%. Conclusions: We found that SUV was associated with TILs in breast cancer and provide clinical evidence that elevated glucose uptake of breast tumors may be affected by TILs in tumor micromileu. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.